INERJA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KOTA MANADO - SINGON, HARIYANTO HAMONANGAN; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: Until recently perceived the public service is not yet running to its full potential, it can even be said to the public servicein Indonesia is still classified as low, due to the absence of consistent and the seriousness of the apparatus of Government inconducting services. It can be seen from the large number of societies that have complained about public services in Indoneisa.With public services that are still lower then required the presence of improved performance to improve the Organization of thepublic service. Similarly, on the issue of settlement also required the existence of a ministry that gives satisfaction to the public.An increase in welfare of society is a major foothold in the determination of policy strategies in regional development. Manadoas the autonomous region is inseparable from social issues that affect the welfare of the community, including increasedpopulation growth in most developing Countires the Central economy often is due to a birth rate high mortality rate followed adecline. Government as scepter should be aware that high birth will affect the various aspects of life in a country or region. Itis to be one of the rationale the Government-backed family planning programs. From the results it can be concluded that theperformance of the Office of Population Control and family planning look at the 5 aspects namely. Productivity, service quality,responsiveness, accountability and corporate responsibility, the success rate is said to have not been able either because thereare still some placement of employees yet keeping with skill or field, and is still the lack of human resources (HRD) everyexisting field. As for the shape of the corporate responsibility of the Office of Population Control and family planning Manadocity in carrying out any work program as well as accountability for any activity carried out by employees of the Department isin compliance with the rules.Keywords: Perfomance, Control Of Population, Family Planning